Local Council of Al Ajaylat Environmental Ebucation as agateway to sustainable development. (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the vole of lnvivonmertal education in achieving sustainable development through the adoption of responsible beharioes that contribute directly to building genuine and comprehensive awaenes arelationship be twen evionmental awarnss and human behavior toward the environment and that eniron mental education plays apositire role in promoting such behaviors it also emphasi the integration of sustainable development cocepts into educational urricula, which contributes to achiering abalanco between sustainable deve lopment and environmental prote ction.